2023
DOI: 10.3390/fermentation9020108
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Alkaline and Heat Pretreatments with Zero-Valent Iron Application in Cassava Pulp and Wastewater for Methane Generation: Development from Batch to Continuous Systems

Abstract: Pretreatment with the addition of metals to anaerobic digestion in biogas production is crucial to address improper degradation of organic compounds with low methane production. Biogas production from a combination of cassava pulp and cassava wastewater in the batch system under the variation of alkaline and heat conditions as a pretreatment was investigated with the zero-valent iron (ZVI) addition after the pretreatment. It was found that alkaline pretreatment at pH 10 with the heat at 100 °C for 30 min combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 102 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…It was in line with the outcome of Puyol, et al [57], which showed that excess ZVI reduced methane production from the AD. Similarly, a previous study using similar wastewater showed that the optimum condition was 50-60 g•ZVI•kg•TVS −1 [48]. This phenomenon may be related to the high accumulation of Fe 2+ and Fe 3+ that inhibit the process of methanogenesis, as the excess attachment may be found in the methanogenesis with the iron ions [46].…”
Section: Biogas Production and Compositionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was in line with the outcome of Puyol, et al [57], which showed that excess ZVI reduced methane production from the AD. Similarly, a previous study using similar wastewater showed that the optimum condition was 50-60 g•ZVI•kg•TVS −1 [48]. This phenomenon may be related to the high accumulation of Fe 2+ and Fe 3+ that inhibit the process of methanogenesis, as the excess attachment may be found in the methanogenesis with the iron ions [46].…”
Section: Biogas Production and Compositionmentioning
confidence: 63%
“…ZVI (Fe 0 ) has been found predominantly with a small portion of iron-carbon (Fe-C) particles based on the peaks observed in the micrograph [47]. The XDR diffractogram was observed at 2θ (Coupled Two Theta/Theta) at the wavelength of 1.54060 in the range of 10-80 • and resulted in peaks that indicated the ZVI at 45 • and 65 • [48]. The structure of the wool was observed to have a diameter of 0.04 mm.…”
Section: Zvi Characterizationmentioning
confidence: 99%
See 1 more Smart Citation